Tracking 40 Million Years of Migrating Magmatism across the Idaho Batholith Using Zircon U-Pb Ages and Hf Isotopes from Cretaceous Bentonites - Jeffrey S. Hannon (Minerals, 2021)
Cretaceous strata preserved in Wyoming contain numerous large bentonite deposits formed from the felsic ash of volcanic eruptions, mainly derived from Idaho batholith magmatism. These bentonites preserve a near-continuous 40 m.y. chronology of volcanism and their whole-rock and mineral chemistry has been used to document igneous processes and reconstruct the history of Idaho magmatism as emplacement migrated across the Laurentian margin. Using LA-ICP-MS, we analyzed the U-Pb ages and Hf isotopic compositions of nearly 700 zircon grains from 44 bentonite beds from the Bighorn Basin, Wyoming. Zircon populations contain magmatic autocrysts and antecrysts which can be linked to the main pulses of the Idaho batholith and xenocrysts ranging from approx. 250 Ma to 1.84 Ga from country rocks and basement source terranes. Initial εHf compositions of Phanerozoic zircons are diverse, with compositions ranging from −26 to nearly +12. Based on temporal trends in zircon ages and geochemistry, four distinct periods of plutonic emplacement are recognized during the Mid- to Late Cretaceous that follow plutonic emplacement across the Laurentian suture zone in western Idaho and into western Montana with the onset of Farallon slab shallowing. Our data demonstrate the utility of using zircons in preserved tephra to track the regional-scale evolution of convergent margins related to terrane accretion and the spatial migration of magmatism related to changes in subduction dynamics.